Godefridus Schalcken : a Dutch painter in late seventeenth-century London - Franits, Wayne (Visual and material culture, 1300-1700., 2018)
In his own day, Godefridus Schalcken (1643?1706) was an internationally renowned Dutch painter, but little is known about the four years that he spent in London. Using newly discovered documents, this book provides the first comprehensive examination of Schalcken?s activities there. The author analyses Schalcken?s strategic appropriations of English styles, his attempts to exploit gaps in the art market, and his impact on tastes in London?s milieu. Five chapters survey his art during these years, concluding with a critical catalogue of all his London-period work.